PENYULUHAN KESADARAN ANAK DAN REMAJA TERHADAP LINGKUNGAN MELALUI WACANA EKOLOGI - Abbas, Sukardi; Nurbaya, Nurbaya; Syawal, Julkarnain; Sahjad, Sumarni; Samad, Sartika (Archipelago, 2023)
ABSTRACTThis dedication presents a detailed overview of how ecological discourse can increase environmental awareness and knowledge among children and adolescents. The aim of this activity is to educate children and teenagers about the importance of protecting the environment, the impact of environmental damage on society, and stopping practices that damage the environment. This service was carried out in Rua Village, Ternate Island District. The results show that children and teenagers are aware of the environmental problems that occur. Environmental problems identified in the Rua sub-district include poor waste management, such as throwing rubbish into the sea, rivers, and beaches; cutting down trees, which results in floods hitting the village; and abrasion, which causes landslides on the coast. After education was carried out, children and teenagers were able to recommend several solutions related to the problems that occurred, such as planting more trees on the coast and in the forest, providing rubbish bins in schools and public places, making and installing notice boards prohibiting littering, and cutting down trees.